2004
DOI: 10.1103/physreva.69.063403
|View full text |Cite
|
Sign up to set email alerts
|

Laser collimation of a continuous beam of cold atoms using Zeeman-shift degenerate-Raman-sideband cooling

Abstract: In this article we report on the use of degenerate-Raman-sideband cooling for the collimation of a continuous beam of cold cesium atoms in a fountain geometry. Thanks to this powerful cooling technique we have reduced the atomic beam transverse temperature from 60 K to 1.6 K in a few milliseconds. The longitudinal temperature of 80 K is not modified. The flux density, measured after a parabolic flight of 0.57 s, has been increased by a factor of 4 to approximately 10 7 at. s −1 cm −2 and we have identified a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
(52 reference statements)
2
24
0
Order By: Relevance
“…This scheme has been tested successfully with FOCS-X to form the pre-cooling lattice "A" described shortly below. Other schemes studied with the same apparatus including grey molasses on the 32 component [21] and Zeemaninduced degenerate Raman sideband cooling (ZIDRSC) [19], [23]. We also demonstrated the use of 2D magneticallyinduced laser cooling as a means to compensate transverse magnetic fields in situ [24].…”
Section: Collimation Of the Atomic Beammentioning
confidence: 79%
See 1 more Smart Citation
“…This scheme has been tested successfully with FOCS-X to form the pre-cooling lattice "A" described shortly below. Other schemes studied with the same apparatus including grey molasses on the 32 component [21] and Zeemaninduced degenerate Raman sideband cooling (ZIDRSC) [19], [23]. We also demonstrated the use of 2D magneticallyinduced laser cooling as a means to compensate transverse magnetic fields in situ [24].…”
Section: Collimation Of the Atomic Beammentioning
confidence: 79%
“…To achieve this, more atoms are launched to begin with thanks to a slow beam pre-source that loads the optical molasses [17], [18]. In addition, improved collimation based on optical lattices [19], [20], [21] means more atoms reach the detection zone after microwave interrogation. The design of FOCS-2 was inspired by experience acquired with FOCS-1 as well as input from auxiliary measurements performed on an experimental fountain dubbed FOCS-X that demonstrated an achievable gain in flux of at least 40.…”
Section: Swiss Continuous Fountain Clocksmentioning
confidence: 99%
“…In Observatoire Cantonal de Neuchâtel, the laser heads shown on figure 1 are employed for studying the basic interaction between atoms and photons, and in particular the effects of AC Stark shift [17], laser recoil induced resonances [18], Sisyphus, adiabatic and degenerate Raman sideband transverse laser cooling of cold atomic beams [19], etc.…”
Section: Basic Research and Precision Laser Spectroscopymentioning
confidence: 99%
“…We used the procedure developped in Ref. [25] to obtain the [26]. Cold atoms are trapped in the potential wells of an optical lattice, their motion is quantized, and n is the vibrational quantum number.…”
Section: A What Limits State Preparation Puritymentioning
confidence: 99%
“…In Ref. [25], we showed that it is possible to adapt this scheme to a continuous beam of cold atoms. However, the resulting quantum state |F = 3, m = 3 is not useful for an atomic clock and thus we would need to replace in this sideband cooling scheme the Zeeman shift by a Stark shift to accumulate all the atoms in |F = 3, m = 0 as proposed in Ref.…”
Section: Introductionmentioning
confidence: 99%